Möglichkeiten der Einbeziehung von Vätern in der Eltern-Säuglings-Psychotherapie - Eickhorst, Andreas; Scholtes, Kerstin (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2011)
How to Involve Fathers in Parent-Infant Therapy - - This paper deals with the role of fathers within a context of parent-infant counseling or therapy. A review of the evidence regarding father-infant interaction and of fathers' involvement in therapeutic intervention is complemented by a case vignette of a young family. It illustrates the different personal characteristics of each parent in their family interaction and delineates options for therapists, notably the useful potentials of fathers.
Gesehen am 11.04.2022
Elektronische Reproduktion der Druckausgabe